Teaching qualification diploma students' orientations towards blended learning of methods of teaching science curriculum in Daraa Governorate through Zoom in educational platform in light of crisis (Damascus University Journal of educational and Psychologyical sciences, 2026)
The research aims at studying teaching qualification diploma students' orientations towards using blended learning of methods of teaching science curriculum through Zoom in educational platform in light of crisis. To achieve this, the experimental approach is used through designing the study tool which is a special questionnaire that its psychometric properties include sincerity and stability have been studied. Then the questionnaire has been applied on the study sample which consists of all teaching qualification diploma students at Third College of Education in Daraa City -they are (22 )students- they all teach science curriculum at schools in in Daraa Governorate and at the same time, they study teaching qualification diploma at Third College of Education in Daraa City   The study has come to a conclusion includes:The degree of diploma students specialized at methods of teaching science towards blended learning is between great and very great.The degree of diploma students specialized at methods of teaching science in mastering educational competencies in blended learning is to a great degree.There are no statistically significant differences in average grades of teaching qualification diploma students towards the questionnaire of teaching qualification diploma students' orientations towards blended learning through Zoom in program in light of crisis according to gender variable.There are statistically significant differences in average grades of teaching qualification diploma students towards the questionnaire of teaching qualification diploma students' orientations towards blended learning through Zoom in program in light of crisis according to years of service and that is in favor of teaching qualification diploma students, specialized in science, who have years of experience from one year to three.There are statistically significant differences in average grades of teaching qualification diploma students towards the questionnaire of teaching qualification diploma students' orientations towards blended learning through Zoom in program in light of crisis according to more years of service, whereas there are no statistically significant differences according to the interaction between the gender variable and years of service.
Keywords: Blended learning; crises; science teaching methods; Diploma Students